Dysregulation of systemic immunity and its clinical application in gastric cancer - Zhang, Yao; Li, Junfeng; Li, Jian; Wang, Jisheng (Frontiers in Immunology, 2024)
Immunotherapy has profoundly changed the treatment of gastric cancer, but only a minority of patients benefit from immunotherapy. Therefore, numerous studies have been devoted to clarifying the mechanisms underlying resistance to immunotherapy or developing biomarkers for patient stratification. However, previous studies have focused mainly on the tumor microenvironment. Systemic immune perturbations have long been observed in patients with gastric cancer, and the involvement of the peripheral immune system in effective anticancer responses has attracted much attention in recent years. Therefore, understanding the distinct types of systemic immune organization in gastric cancer will aid personalized treatment designed to pair with traditional therapies to alleviate their detrimental effects on systemic immunity or to directly activate the anticancer response of systemic immunity. Herein, this review aims to comprehensively summarize systemic immunity in gastric cancer, including perturbations in systemic immunity induced by cancer and traditional therapies, and the potential clinical applications of systemic immunity in the detection, prediction, prognosis and therapy of gastric cancer.